A taxonomy of open government data research areas and topics. Issue 1 (2nd April 2016) - Charalabidis, Yannis; Alexopoulos, Charalampos; Loukis, Euripidis
ABSTRACT: The opening of government data, in order to have both social and economic value generated from them, has attracted the attention and interest of both researchers and practitioners from various disciplines, such as information systems, management sciences, political and social sciences, and law. Despite the rapid growth of this multidisciplinary research domain, which has led to the emergence and continuous evolution of technologies and management approaches for open government data (OGD), a detailed analysis of the specific areas and topics of this research is still missing. In this article, a detailed taxonomy of research areas and corresponding research topics of the OGD domain is presented: it includes four main research areas (ODG management and policies, infrastructures, interoperability and usage and value), which are further analyzed into 35 research topics. An important advantage of this taxonomy, beyond its high level of detail, is that it has been developed through extraction and a combination of relevant knowledge from three different sources: important relevant government policy documents, research literature, and experts. For each of the 35 research topics we have identified, its research literature is summarized and main research objectives and directions are highlighted. Based on the taxonomy, an extension of the extant OGD lifecycle is advanced; also, under-researched topics that require further research are identified.